2007
DOI: 10.1523/jneurosci.0777-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Folding Abnormalities in Autism Revealed by Surface-Based Morphometry

Abstract: We tested for cortical shape abnormalities using surface-based morphometry across a range of autism spectrum disorders (7.5-18 years of age). We generated sulcal depth maps from structural magnetic resonance imaging data and compared typically developing controls to three autism spectrum disorder subgroups: low-functioning autism, high-functioning autism, and Asperger's syndrome. The lowfunctioning autism group had a prominent shape abnormality centered on the pars opercularis of the inferior frontal gyrus tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(231 citation statements)
references
References 72 publications
21
206
3
1
Order By: Relevance
“…Moreover, our data provide the first anatomical evidence of a compromised structure of the temporoparietal cortex predicting social dysfunctions in ASD, highlighting the behavioral significance of ASD-related structural changes. Regional gray matter changes in ASD, however, might vary, for example as a function of age or diagnostic subgroup (Brambilla et al 2003;Nordahl et al 2007;Amaral et al 2008). Here we only investigated adult highfunctioning individuals with ASD, and our conclusions are limited by a rather small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our data provide the first anatomical evidence of a compromised structure of the temporoparietal cortex predicting social dysfunctions in ASD, highlighting the behavioral significance of ASD-related structural changes. Regional gray matter changes in ASD, however, might vary, for example as a function of age or diagnostic subgroup (Brambilla et al 2003;Nordahl et al 2007;Amaral et al 2008). Here we only investigated adult highfunctioning individuals with ASD, and our conclusions are limited by a rather small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found gray matter increases in some of these and other regions in ASD, making the current picture on structural brain differences in ASD somewhat inconsistent (Amaral et al 2008). These inconsistencies may be related to the recently often discussed heterogeneity in the spectrum, as well as between-study differences with respect to functionality and age of the ASD group (Brambilla et al 2003;Nordahl et al 2007;Amaral et al 2008;Nickl-Jockschat et al 2011). …”
Section: Regional Gray Matter Abnormalities and Their Correlation Witmentioning
confidence: 99%
“…Some SBM approaches estimate the outer cortical surface relying on the accuracy of the inner cortical surface and assuming that the outer cortical surface has a similar shape as the inner one. Subsequently, they select the mid-cortical surface [8] which is even more similar to the inner cortical surface than the outer surface.…”
Section: Cortical Surface Delineationmentioning
confidence: 99%
“…Levitt et al [7] create maps of 22 major sulci and report anatomical shifts for some sulci in frontal and temporal lobes. Nordahl et al [8] report increased sulcal depths for autistic subjects in the operculum and the intraparietal sulcus using surface-based morphometry (SBM). They found all abnormalities to be more pronounced in children than adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, magnetic resonance (MR) imaging has enabled in vivo studies of human cortical folding patterns. One class of approaches to folding analysis rely on spatial normalization [1,2] and subsequently perform statistical hypothesis testing at every voxel or surface element in the normalized space. However, the difficulty in finding sufficiently-many homologous features [3,4] may directly affect the normalization and, thereby, the reliability of findings in the clinical study.…”
Section: Introductionmentioning
confidence: 99%